Faktor Penghambat Inovasi Pelayanan Si Rancak Berbasis Online dalam Memberikan Pelayanan Prima Kepada Masyarakat - Rahayu, Oktavi; Malau, Hasbullah (Policy, Law and Political Research Center, 2023)
Since the Covid-19 pandemic, everyone including the government has implemented WFH (Work From Home) or working from home. This condition forces people to be able to adapt to new technology and habits so they can continue to live life as they should. Thus, in order to support the smooth running of services to the community, the head of the Padang City population and civil registration service published an online service application called Si Rancak. However, it cannot be denied that there are still several problems or inhibiting factors in providing services to the community. This research aims to explain what are the inhibiting factors of Si Rancak's online-based service innovation to provide excellent service to the community in the Padang City Dukcapil Office. The research method used is qualitative research. The types and sources of data used in this research are primary data and secondary data. Testing the validity of this research data uses source triangulation and method triangulation techniques. The analysis technique is using data reduction, data presentation, and drawing conclusions. The results of this research show that there are internal and external factors that hinder the public's access to the Si Rancak application. Internal factors such as people not having smartphones, not understanding information technology, age factors, educational and employment status, and disabilities. Meanwhile, external factors such as unstable internet network problems.